Experimental Study of Glued Laminated Timber (Glulam) from Jackfruit Wood and Coconut Wood for Timber Beams of Level Houses in East Nusa Tenggara - Handika Setya Wijaya; Yurnalisdel; Diana Ningrum; Galih Damar Pandulu; Yerian Hamba Banju (PT FORMOSA CENDEKIA GLOBAL, 2023)
Wood is a construction material that is familiar to the wider community. Wood can be used in construction. The purpose of this study was to determine the specifications of the physical properties, mechanical properties, tensile strength and flexural strength of laminated wood (glulam), in jackfruit and coconut wood beams originating from the East Nusa Tenggara region in multi-storey house buildings. The tests carried out included testing the water content, testing the tensile strength and bending strength, testing the tensile strength and bending strength on glulam beams using epoxy glue adhesives. The results of this study showed that jackfruit wood and coconut wood aged 15 years and 20 years had an average moisture content of 15 years, namely 15% and 26%, the average specific gravity was 0.54 (tons/m3) and 0.46 (tons/m3). Meanwhile, the average water content for 20 years is 15% and 32%, the average specific gravity is 0.58 (Ton/m3) and 0.45 (Ton/m3). The tensile strength of intact and glulam wood of jackfruit and coconut wood was obtained from laboratory results on SNI 7973-2013 calculations, the average tensile strength of intact jackfruit and coconut wood was 84.40 MPa and 80.73 MPa. The flexural strength of intact beams and glulam of jackfruit and coconut wood aged 15 years was obtained from laboratory results on SNI 7973-2013 calculations of the flexural strength of intact beams for 15 years, the average being 71.81 MPa and 26.07 MPa. At 15 years of age, the flexural strength of glulam beams was the highest variation 1 and variation 2 (Jackfruit, Coconut, Jackfruit) mean 76.00 MPa and 41.85 MPa. The flexural strength of intact beams and gulam of jackfruit and coconut wood aged 20 years was obtained by laboratory results on SNI 7973-2013 calculations of flexural strength of intact beams, which were 80.27 MPa and 29.73 MPa respectively. At the age of 20 years, the highest flexural strength of glulam beams were variations 1 and 2 (Coconut, Jackfruit, Coconut) with an average of 80.40 MPa and 48.76 Mpa.